NLRP12/C1qA positive feedback in tumor-associated macrophages regulates immunosuppression through LILRB4/NF-κB pathway in lung adenocarcinoma - Jiaxin Yin; Yuxiao Song; Yang Fu; Jun Wang; Zhimin Zhang; Shasha Ruan; Gaoli Liu; Bicheng Zhang (Cancer Immunology, Immunotherapy)
Abstract The anti-tumor immune response is greatly hindered by the protumor polarization of tumor-associated macrophages (TAMs). Cancer-related inflammation plays a central role in TAMs protumor polarization. Our study explored the unique positive feedback loop between inflammasome and complement in TAMs. The present study identified NOD-like receptors family pyrin domain containing 12 (NLRP12) formed positive feedback with C1qA and drove TAMs protumor polarization via the LILRB4/NF-κB pathway. In addition, NLRP12 was predominantly expressed in TAMs and was associated with poorer prognosis in lung adenocarcinoma (LUAD) patients. Knocking down LILRB4 inhibited TAMs protumor polarization. NLRP12-overexpressing TAMs promoted tumor cells’ malignant progression and inhibited T cells’ proliferation and cytotoxic function. Lastly, NLRP12 knockout (NLRP12−/−) reversed macrophage polarization, enhanced T-cell anti-tumor immunity, and suppressed tumor growth. Our findings highlighted the essential role of NLRP12/C1qA positive feedback loop and the LILRB4/NF-κB pathway in promoting TAMs protumor polarization. Inhibition of NLRP12 suppressed tumor development and promoted immune response. NLRP12 may be a promising target for LUAD immunotherapy.